A study on the application of natural extracts as alternatives to sodium nitrite in processed meat. Issue 3 (17th January 2022) - Grispoldi, Luca; Karama, Musafiri; El‐Ashram, Saeed; Saraiva, Cristina; García‐Díez, Juan; Chalias, Athanasios; De Gennis, Matteo; Vannuccini, Andrea; Poerio, Giusi; Torlai, Paolo; Chianese, Giuseppina; Fermani, Anna G.; et al.
Abstract: Consumers are increasingly interested in purchasing meat products with low food additives content or even without the, since these kind of foodstuffs are perceived as more natural and healthier. Nitrites are the most commonly used additives in the meat industry to prevent the growth of pathogenic bacteria, keep red color (secondary effect on myoglobin = iron and oxygen‐binding), and improve flavor. In this scenario, meat processors are challenged to produce nitrite‐free products guaranteeing the microbial quality and sensory characteristics. The objective of the present study was to determine the effect of various natural extracts against the color of thermal processed beef, manufactured without nitrites. A total of fourteen natural alternatives have been evaluated: capsicum extract liquid phase (capsanthin), paprika oleoresin liquid phase, monascus yellow powder ( Monascus purpureus ), red yeast rice powder ( Monascus purpureus ) from three different producers, lycopene powder, red beet juice powder ( Beta vulgaris ), rosemary extract ( Rosmarinus officinalis ), capsicum extract powder (capsanthin), carmine pigment powder (cochineal extract), sorghum red pigment powder ( Sorghum bicolor ), and two factory‐supplied recipes. For the first trial, extracts were added at a concentration of 0.3% in canned meat without nitrite. Samples were analyzed by colorimetric measurements before and after sterilization. The aim was to find natural extracts that provide similar color characteristics as canned meat with nitrite (used as reference). After color analysis, the extracts that did not show statistically significant differences ( p > .05) from the positive control were chosen for the second trial, consisted of sample preparation at three different concentrations of extract (0, 1%, 0, 2%, and 0, 3%) following factory manufacture procedures to ensure that the results were as accurate as possible. Results showed that sorghum red pigment powder ( Sorghum bicolor ) provides stable pigments and can be added as a natural additive to the manufacture of traditional canned meat recipe to maintain a similar red/pink color as same as provided by sodium nitrite. Novelty impact statement: Producers are trying to obtain meat products without nitrites that maintain the same level of microbial safety and the typical color. In this study, we analyzed the effect of adding different natural extracts on the color of canned meat made without nitrites. The powder extracted from sorghum husks ( Sorghum bicolor ) can be added to the classic canned meat recipe to obtain a product that maintains the typical red/pink color.